Risk Based Capital Factors’ Impact for Reinsurance’s Business and Profitability - Iga Permata Putri Mentari; Rahmat Aryo Baskoro (Eduvest - Journal of Universal Studies, 2023)
Reinsurance is one of important aspect from insurance business. To ruin their business, insurnaces don’t only rely on their capacity, but to their back up capacity behind them. For arising financial strength and intercalation to Indonesia’s GDP, OJK as regulatory has obligatory for insurance to ceded their insurance cession to domestic Reinsurance. Insurance business would be always linked with reinsurace due to their requirements for spreading risk (by reduce the variability of the financial costs to insurance companies arising from the claims). The prior researches give indicator that financial strenght will affect how sevice company ruin their business and profitability making. This paper aim to empirically inquire intercouse between financial strength of the company with their running business. Financial strenght for reinsurance business is the most important component due to their business characteristic, business to business. RBC as one of the parameter will be the one which impose the insurance company to lay their business. So with RBC’s component we could inquire how reinsurance’s business and profitability. This study used quantitative research method. The analysis framework is based on relationship between risk based capital’ factor in reinsurance with their business and profitability effectivity. Data will be provided secunderly by companies annual report with total 5 local reinsurance in Indonesia. And will be examined by regression model. The finding will indicate how Risk Based Capital’s factor involve business and profitability both for reinsurance company. The findings may help industry to better understand how financial power’ factor work for profitability.